Upaya Pemenuhan Permintaan Premix di PT Japfa Comfeed Indonesia Tbk dengan Perencanaan Agregat - Marco Gunawan (Jurnal Titra, 2020)
Premix Plant is a plant in PT Japfa Comfeed Indonesia Tbk which produces premix for animal feed ingredient. Premix’s demand increases approximately 12% a year. Hence, premix plant must prepare the solution to meet their demand. In 2020, premix plant production capacity is not sufficient enough for their demand. Thus, preparation like overtime and adding new shifts are considered for escalating production capacity. On the other hand, there are costs for overtime and adding new shifts. Therefore, aggregate planning is used for deterring overtime hours and when to add new shifts. Aggregate planning concept will be implemented in open solver and ProModel to ease the calculation. The calculation result shows overtime is used until the end of 2020 and new shifts are added in early 2021. This new shift will cause overproduction due to the increase of capacity. Therefore, premix will not be produced in full for a day. The rest of the time will be used to weigh feed additive. That solution will cost nearly Rp 11,152,462,807.50 per five years.